1997
DOI: 10.1111/j.1528-1157.1997.tb01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Cardiac Function in Patients with Temporal Lobe Epilepsy: Different Roles of EEG‐ECG Monitoring and Spectral Analysis of RR Variability

Abstract: Summary: Purpose: Because several reports have described the relation between epilepsy and cardiac arrhythmias and suggest that changes in autonomic neural control of the heart could be involved in the pathogenesis of sudden unexplained death in patients with epilepsy, the aim of this study was to evaluate cardiac function in patients with temporal lobe epilepsy.Methods: Sixty-five patients with epilepsy were evaluated by simultaneous ambulatory 24-h EEG-ECG monitoring, and in 30 of these, power spectral analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
100
2
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 29 publications
11
100
2
6
Order By: Relevance
“…Autonomic dysfunction has also been noted in the interictal period, could be the only sign during this phase of clinical calm, and might play an important role in the cause of Sudden unexpected death in epilepsy (SUDEP) (25,26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic dysfunction has also been noted in the interictal period, could be the only sign during this phase of clinical calm, and might play an important role in the cause of Sudden unexpected death in epilepsy (SUDEP) (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in HRV vary between seizure types; for example in temporal lobe seizures, increased sympathetic and decreased vagal heart rate modulation often precedes ictal electroencephalographic (EEG) changes (27)(28)(29). Previous studies have reported diminished interictal HRV in temporal lobe epileptic patients using conventional short and long-term electrocardiogram (ECG) recordings, but general study with focused on changes in heart rate during pre-ictal phase failed, and many aspects of it has remained unclear (25,(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, active research into brain waves, which can objectively estimate brain function, is progressing. Since a brain mapping function was recently added to the electroencephalogram (EEG) measurement system, not only is judgment based on visual aids made possible, but quantitative numeric values can now also be shown 4,5) . This quantitative electroencephalogram (qEEG) analysis can be used by non-specialists, and provides instant information from the EEG computer equipment 6) .…”
Section: Introductionmentioning
confidence: 99%
“…A monitorização vídeo-ECG/EEG é o melhor método para a diferenciação entre epilepsia e quadros sincopais 23 . A identificação de crise epiléptica causando arritmia cardíaca é necessária, pois implica em terapêutica específica.…”
Section: Discussionunclassified